Women’s work: Women leading women in a teaching-focussed first year college - Konjarski, Loretta; Fletcher, Julie; Husaric, Maja; Kelly, Kate; KonYu, Natalie; Tangalakis, Kathy (Journal of University Teaching and Learning Practice, 2022)
In 2018, a community of practice initiative was introduced to enhance the career opportunities for the 53 women academics in the First Year College (FYC) at Victoria University. The FYC is a teaching-oriented college and thus the traditional career advancement through research is largely not applicable to women in the college – many of whom are teaching-focussed academics. The Women in First Year (WiFY) executive developed and implemented workshops with the aim of aiding women on their career trajectory and in getting more women to senior levels and into leadership positions. In this article we will argue that the WiFY initiative has resulted in greater career achievements for women in the FYC. Using data collected from semi-structured interviews as well as relevant research and FYC statistics on career progression, we will argue that WiFY has had a positive effect on the career trajectory of women in the FYC who have participated in their workshops.